Mulberry leaves treated with bordeaux mixture protect silkworm caterpillars against fungal and viral diseases - Fernandes, Juliana [UNESP]; Brancalhão, Rose Meire Costa; Nicodemo, Daniel [UNESP]; De Fátima Chasko Ribeiro, Lucinéia; Santorum, Marilucia [UNESP] (Universidade Estadual de Londrina, 2016)
The bordeaux mixture is used as a natural agricultural fungicide, and its application in sericulture can benefit the production of silkworm cocoons, Bombyx mori (Lepidoptera: Bombycidae). The aim of this study was to verify whether the bordeaux mixture exerts a protective effect in B. mori against fungal and viral diseases. This experiment was performed during two seasons, autumn and spring, in which 7,500 caterpillars were used at the beginning of the third instar and divided into five groups, with three repetitions of 500 individuals each. In the three groups, the caterpillars were fed leaves of Mulberry (Morus spp.) that were enriched with an aqueous bordeaux mixture solution at concentrations of 5, 10 and 20%. One group was fed exclusively mulberry leaves (control), and another was fed leaves that were moistened with water. Fungal contamination was evaluated in the integumentary surface of the insect and the mulberry leaves in the bed of creation by checking the number of colony-forming units (CFU). In the analysis of viral contamination, 20 caterpillars from each group at the beginning of the fifth instar were inoculated with 10 ìl of a suspension of Bombyx mori nucleopolyhedrovirus (BmNPV). Daily, from the second to the ninth day after inoculation (dai), two caterpillars of each group were anesthetized and formalin-fixed 7% for microscopic processing and viral cytopathology analysis. A completely randomized design was used, and the CFU were compared by Tukey test with 5% significance. The results showed a decrease of 55.1% in CFU present on the mulberry leaves in the fall, when the 5% bordeaux mixture solution was used. There was no significant difference between the groups based on the bordeaux mixture in this period. During the same period, reductions of CFU of 28.5, 74.9 and 74.4% were verified in the integument of B. mori when bordeaux mixture solutions of 5, 10 and 20% were used, respectively, compared with the data that were obtained in the control group. In the spring, no difference was observed between the groups that received bordeaux mixture solution and the control. In the case of BmNPV, the 10% bordeaux mixture solution promoted greater resistance to viral infection, possibly favoring the activation of defense mechanisms of insects. Therefore, we recommend the use of a 10% bordeaux mixture solution in mulberry leaves to control fungal and viral diseases in silkworm rearing.
Keywords: Baculovirus; Bombyx mori; Lepidoptera; Sericulture